Estudio del estado del Arte de tres tipos de desamargado (tradicional, fermentación y germinación), de dos Ecotipos de Chocho (lupinus mutabilis sweet) y de dos Índices de madurez, para determinar su factibilidad. - Calupiña Jácome, Xavier Alexander (2020)
This research contains a bibliographic compilation about three methodologies for the debittering of lupine: traditional, fermentation, and germination to reduce the alkaloid content in lupine since these compounds cause a bitter taste, which is toxic. To reduce alkaloids, the traditional method establishes soaking, cooking, and washing processes. The maturity indices of the grain: tender and dry, were reviewed in previous research at the Technical University of Cotopaxi to establish methodologies for debittering: fermentation and germination, with their respective quality parameters and flow charts for each maturity index. A guide was developed that will allow the lupine harvest and post-harvest management project to continue. The methodologies of the primary physicochemical analyzes of lupine were described, such as determining the percentage of alkaloids, pH, moisture, and protein, and the main microbiological analyzes, such as total coliforms, fungi and yeasts, and Escherichia coli. The research identified the best alkaloid extraction methods based on the Ecuadorian Technical Standard, which "establishes a range of 0.02-0.07% alkaloid content to be able to consume it without risk of intoxication." (NTE INEN 2390: LEGUMINOSAS. GRANO DESAMARGADO DE CHOCHO REQUISITOS, 2004, p. 2) Some methodologies were established for the production processes of four agri-food proposals such as empanadas, fermented drink, 'tempeh, ' and 'buñuelos' using two different ecotypes of lupine: local and local Peruvian, each process contains a flow diagram. The consumption of lupine is limited to the combination with 'tostado,' ceviche, and adding chili. A cost analysis was carried out to verify the feasibility of the project by reducing the alkaloid content of the lupine by the different types of debittering: traditional, fermentation, and germination, being debittering by germination method is the most feasible.